INTENTION TO USE ELECTRONIC FOOD ORDERING AMONG UNIVERSITIES STUDENTS IN KUALA TERENGGANU - Noorazlin Ramli; Nur Aisyah Syafiqah Muhammad Khairi Sham; Nur Farthiha Binti Mohamad; Fatimah Abd Ghani; Wan Nazriah Wan Nawawi (International Journal of Accounting, Finance and Business, 2020)
Electronic or online food ordering is the one of the technology that has been developed to ease the food business. Therefore, the purpose of this paper is to determine the students’ intention to use electronic food ordering in Kuala Terengganu. The quantitative method was applied through a questionnaire survey. 120 questionnaires were distributed to the respondents that were randomly selected in two universities in Kuala Terengganu namely Universiti Sultan Zainal Abidin (UniSZA) and Universiti Teknologi Mara (UiTM). 100 questionnaires out of a total of 120 questionnaires were completed and returned with reliable and meaningful results. The result clearly shows that majority of the students were have a positive intention to use electronic food ordering due to perceived convenience, customer control, attractive marketing and eagerness to use technology. Besides, they feel that electronic food ordering is user-friendly and they can get sufficient information to order. Hence, this study is vital in providing knowledge and information about the significance of electronic food ordering to the food industry player especially to the food operator and manufacturer. In line with that, it will help community and local people in expanding their business and make advantage of electronic food ordering as one of the marketing strategy and reduce unemployment rate thus contribute to a better national income.